Role of Supervisory Support and Management Commitment to Service Quality: The Influence of Supervision and Management on Service Quality (Journal of Advances and Scholarly Researches in Allied Education, 2011)
There is no roomfor debate over the rising importance of services in today’s world. This hasbeen established well in the previous chapter on review of literature byvarious researchers over the time. The service sector dominates the economiesworld over. India is no exception. We as a nation are developing and beingactive members in the world trade, we need to know the rules of the game.Presently, the Indian service sector is in a developing state. The competitionat such stages ought to be intense. To achieve a competitive advantagecompanies, are striving hard to develop competencies. The capabilities in theform of human resources are a must for every firm focusing on providing qualityservices to secure a competitive edge. The human resource practices of a firmand employees behaviour may affect the quality of services. Moreover, it isimperative for any organization to provide quality services to secure customerloyalty which is important for the firm performance.